UNDERSTANDING THE COGNITIVE PROCESSES OF DISTANCE LEARNING STUDENTS: IMPLICATIONS FOR EDUCATION AND INSTRUCTIONAL DESIGN - Zokhidov Samandar (Scholar Express Journal, 2024)
Distance learning has become an increasingly prevalent educational modality, offering flexibility and accessibility but also presenting distinct cognitive demands for students. This article examines the cognitive processes involved in distance learning, drawing upon research from cognitive psychology, educational technology, and related fields. Key concepts explored include self-regulated learning, metacognition, motivation, and the role of technology-mediated interactions. The article highlights both challenges and opportunities associated with distance learning's impact on cognition, providing insights to support effective instructional design and student success in this context
Keywords: Self-regulated learning; metacognition; motivation